2016
DOI: 10.1186/s12870-016-0721-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling analysis for two Tibetan wild barley genotypes in responses to low nitrogen

Abstract: BackgroundNitrogen (N) is the most common limiting factor for crop productivity worldwide. An effective approach to solve N deficiency is to develop low N (LN) tolerant crop cultivars. Tibetan annual wild barley is well-known for its wide genetic diversity and high tolerance to poor soil fertility. Up to date, no study has been done to illustrate the mechanism of LN tolerance underlying the wild barley at transcriptional level.ResultsIn this study, we employed Illumina RNA-Sequencing to determine the genotypic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 66 publications
8
64
1
Order By: Relevance
“…Two genes were downregulated while the other ten showed increased expression under N-stress. Two of these transporters are orthologous to the ones differentially expressed in N stress conditions in barley, recently described 18 . Among the DE transporters responsive to ammonium, two orthologues to AMT3-1 from barley were upregulated in durum wheat stressed roots, while one orthologue to Arabidopsis AMT2 was downregulated in stressed roots and one orthologue to Arabidopsis AMT1-4 was upregulated in both stressed flag leaf and leaf/stem tissues (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two genes were downregulated while the other ten showed increased expression under N-stress. Two of these transporters are orthologous to the ones differentially expressed in N stress conditions in barley, recently described 18 . Among the DE transporters responsive to ammonium, two orthologues to AMT3-1 from barley were upregulated in durum wheat stressed roots, while one orthologue to Arabidopsis AMT2 was downregulated in stressed roots and one orthologue to Arabidopsis AMT1-4 was upregulated in both stressed flag leaf and leaf/stem tissues (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the transcriptomic approach has been widely used recently thanks to its high sensitivity and reproducibility in a number of different species (model and non-model) and experimental conditions 1214 . Studies concerning cereal responses to nitrogen starvation have been also carried out partially unveiling differential expressed genes (DEGs) involved in these processes for instance in sorghum, rice, barley, and wheat 1518 . However, the mechanisms regulating N use efficiency (NUE) in wheat (bread and durum) need to be further investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcription factors (TFs) are well-known to be crucial for the regulation of gene expression at the transcriptional level and are responsive to environmental cues by binding to corresponding cis-elements of target genes [52]. In our research, DEGs encoding transcription factors mainly belonging to 14 families were identified, and almost all of them had been previously determined in transcriptional analysis in many plant species [53][54][55]. Among these, ERF, WRKY, bHLH, MYB, NF-Y, and Trihelix families were responsive under N, P, and K starvation conditions.…”
Section: Differential Expressed Transcription Factors May Regulate Mementioning
confidence: 94%
“…In low potassium treated tobacco, 3 cytochrome P450 members were also up-regulated [37]. The DEGs belong to cytochrome P450 family were also detected from potassium deficiency tomato [38], low-N polar [39], rice [40], sorghum [41] and wild barley [42]. Cytochrome P450 family genes were reported to participate in the biosynthesis of lignin precursors or hormone homeostasis [43], involved in the formation of cell wall and regulated the plant growth [44].…”
Section: Discussionmentioning
confidence: 99%